Navigating Unethical Practices and Ethical Dilemmas: A Qualitative Study of Middle‐Level Academic Leadership in Pakistan - Shahzadi, Shazia; Juhary, Ali; Shah, Syed Shoaib; Munir, Naureen; Farooque, Muhammad Anees (2024)
This article presents the qualitative findings of a study investigating the experiences of middle-level academic leaders with unethical practices and ethical dilemmas in their everyday work. An electronic survey was conducted with academic leaders from universities in various cities across Pakistan. The study reveals three key findings. Firstly, the complex environment within universities creates a fertile ground for ethical dilemmas to arise. Secondly, participants identified two primary types of unethical practices: educational deceit and incorrect behavior directed towards workforce team and students. Finally, the ethical dilemmas highlighted in the study centered on the conflict between the academic leaders' strong professional ethics and an ethic of care, as well as their adherence to supervisors' directives and institutional rules and policies.